P623 The impact of SARS-CoV-2 outbreak on the treatment adherence and clinical outcome of patients with inflammatory bowel disease treated with biological agents. (27th May 2021) - Martino, G; Carparelli, S; Marseglia, A; Pastore, M R; Placentino, M; Nardella, M; Guerra, M; Palmieri, O; Latiano, A; Perri, F; Ercolino, F; Bossa, F
Abstract: Background: The SARS-CoV-2 pandemic has led to a remodeling of care activity, including the inflammatory bowel disease (IBD) centers. According to international recommendations, we did not discontinue immunosuppressive or biologic drugs and reorganized biologic drug infusions' administration to minimize the risk of infection. The aim of this study is to describe the clinical outcome of SARS-CoV-2 infection and the adherence to the scheduled biologic therapies in a single tertiary center including both IBD adult and pediatric patients treated with biological agents during COVID-19 pandemic. Methods: Demographic information, clinical data and the adherence to the therapy were collected in all consecutive IBD patients treated with biologic agents from March 2020 to February 2021. Moreover, we reported the clinical outcome of IBD patients infected with SARS-CoV-2. Results: A total of 278 subjects (171 male) treated with a biologic agent (34 children) were included. The mean age was 41.6 ± 17.3 years (range 5 – 88), and the mean disease duration was 12.7 ± 10.1 years (range 0.2 – 49). One hundred eleven patients (39.9 %) had ulcerative colitis, and 167 (60.0 %) had Crohn's disease. About the therapy: 73 patients were receiving infliximab, 93 adalimumab, 20 golimumab, 59 vedolizumab, 29 ustekinumab, and 4 an experimental compound. 31 patient, including 1 child, (11.1 %) were treated with combination therapy. The mean Charlson Comorbidity Index was 1.5 (range 0 – 8). Twenty one patients (2 pediatrics and nineteen adults) (7.5 %) had a confirmed diagnosis of SARS-COV-2 infection. Only one of them (an adult man) was hospitalized but did not require intensive care unit measures. Compared to cumulative SARS-CoV-2 infection in the general population in our Region, the cumulative incidence of SARS-CoV-2 infection in our cohort was significantly higher (7.5% vs 4.0%, p < 0.002). Twelve adult patients (4.3%) postponed biologic therapy for fear of SARS-CoV-2 infection during the first wave of the pandemic, and two of them (16.6%) experienced a clinical relapse. Conclusion: In our cohort, the adherence to biologic therapy was high during the pandemic, but the rate of clinical relapse in patients who postponed the scheduled administration of therapy was relevant. Although the incidence of SARS-CoV-2 infection was significantly higher than in general population, the clinical impact was mild as no patients experienced a severe form of COVID-19.